The Flight of the All-One to the All-One: The phygē monu pros monon as the Basis of Plotinian Altruism - Tolan, Daniel J. (Harvard theological review, 2021)
It has become commonplace to contrast Plotinus’s spirituality with Christian spirituality by portraying the former as solipsistic and the latter as communal. In particular, this critique has centred around Plotinus’s description of mystical ascent as a "flight of the alone to the alone" and his presentation of Plato’s Phaedrus as an exhortation to "work on your own statue." Yet, should one understand the One as a supreme unity, it would appear that the Plotinian unio mystica renders the mystic supremely unified with the rest of being. Accordingly, this article emphasizes Plotinus’s "inclusive monotheism" in order to argue that the "flight of the alone to the alone" should be understood as a movement towards the supreme unity that underlies reality. The unificatory effects of this ascent are emphasized by the way in which Plotinus, in both his life and works, depicts teaching as a common response to henosis. This didactic turn, it is argued, is a response to glimpsing the deep unity of reality, which expands the mystic’s sphere of concern to include the "other" as another self.